Tetrahydronaphthalenes by Enantioselective Migratory Suzuki–Miyaura Cross-Coupling of meso Bis(Boronic Esters) - Lee, Paul; Eugene, Bill D.; Allais, Christophe; Singer, Robert A.; Morken, James P. (Synthesis, 2025)
In the presence of chiral palladium complexes, the enantioselective catalytic Suzuki–Miyaura reaction of meso diboryltetrahydronaphthalene was found to occur with chain-walking. This process provides access to compounds with a 1,3 relationship between the cross-coupled aryl group and the remaining boronic ester. The reaction was applied toward the synthesis of pharmaceutically relevant targets and provides a simple inroad to enantiomerically enriched materials.
Keywords: Organoboron; Asymmetric catalysis; Asymmetric synthesis; Cross-coupling; Catalysis